THE VITAL ROLE OF PERIODONTAL HEALTH IN DIABETES MANAGEMENT (International Seven Journal of Multidisciplinary, 2024)
The analysis underscores the critical importance of periodontal health in managing diabetes mellitus, a chronic condition affecting millions globally. It highlights the intrinsic link between oral health and glycemic control, along with the complications associated with diabetes. As evidence suggests, untreated periodontal issues in diabetic patients significantly increase the risk of complications that may lead to hospital admissions. Chronic inflammation from periodontitis exacerbates glycemic control, creating a detrimental cycle that further compromises patient health. The need for an integrated approach that incorporates periodontal health as a fundamental aspect of diabetes treatment is emphasized. Implementing screening and treatment programs for periodontal health can improve patients’ oral conditions while yielding substantial savings for healthcare systems by reducing hospitalization rates and associated costs. Education plays a vital role, as increasing patient awareness about the connection between oral health and diabetes encourages better self-care practices, ultimately leading to improved health outcomes. Research findings reinforce that effective periodontal treatment benefits not only oral health but also contributes to lowering diabetes-related complications and healthcare expenses. The conclusion drawn is that integrating dental care with diabetes management is essential for optimizing patient health, enhancing quality of life, and relieving the burden on healthcare systems. By prioritizing periodontal health, healthcare providers can help mitigate the impact of diabetes and improve overall patient outcomes.